Allergic contact stomatitis masquerading as apthous stomatitis: a case report - Sharma, Shivani; N., Rakesh; Sharma, Shweta (International Journal of Scientific Reports, 2017)
Allergic contact stomatitis is a rare disorder, which most clinicians are not familiar with. These lesions may be indistinguishable clinically and histopathologically from various other lesions. We present a case of a young female who visited us with a complaint of painful ulcers over her tongue for the past 5 days. After a thorough history and clinical examination, a provisional diagnosis of apthous stomatitis was made and treated accordingly but with no relief. On carefully eliciting the history again, the patient confirmed using a new herbal toothpaste. The patient was advised topical corticosteriods and to avoid the new toothpaste. All the lesions healed completely in a week.